Green development status in Zhejiang province and the city of Ningbo, China: examination of policies, strategies and incentives at multiple levels - Cheshmehzangi, Ali; Deng, Wu; Zhang, Yun; Xie, Linjun (IOP Publuishing, 2017)
China is undergoing the largest scale of urbanization in history and at an unprecedented pace. The construction and operation of buildings have inevitably brought severe pressures on resource conservation and environmental protection. China has initiated policies, strategies and financial incentive schemes at national level to address these issues. It is also seen that there is a growing interest in recent years at local government level in promoting green buildings. This paper will examine the current national policies, targets and standards and then discuss how these national initiatives are reflected at provincial and city level by taking Zhejiang Province and Ningbo City as case studies. A comparison between different levels of initiatives is conducted by reviewing incentive mechanisms, technological development and compliance requirements. It is concluded that the national initiatives may be not effective without local enhancement. © Published under licence by IOP Publishing Ltd.